STUDI KANDUNGAN SENYAWA KIMIA TUMBUHAN OBAT DI DESA LEGOKHUNI DAN SUKADAMI KABUPATEN PURWAKARTA - Abriyani, Ermi; Fikayuniar, Lia; Zulfa, Amanda Auliya (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
A study on the chemical compound content of medicinal palnts was conducted in Legokhunimand Sukadami Villagesa, Purwakarta Region. The aim of this study was to examine the chemical compound found in various plants used as traditional medicine in Legokhuni and sukadami Villages in Purwakarta Region. The method used involved interviewing several residents from both villages regarding the traditional medicines they used, and performing phytochemical screening assay using specific reagents. The results of this study showed there 33 types of medicinal plants identified through interviews. The phytochemical screening revealedthat the most commonly found secondary metabolites in these palnt were alkaloids and flavonoids, each present in all33 palnt species. Quinoneswere found in 24 plant species, phenolics and tannins in 26 species, and saponins in 30 species. These plant types are therefore considered promising candidates for further in-dept research.